A Microflow Cytometer with a Rectangular Quasi-Flat-Top Laser Spot - Zhao, Jingjing (Sensors (Basel), 2016)
This work develops a microflow cytometer, based on a microfluidic chip for three-dimensional (3D) hydrodynamic focusing and a binary optical element (BOE) for shaping and homogenizing a laser beam. The microfluidic chip utilizes sheath flows to confine the sample flow along the channel centerline with a narrow cross section. In addition to hydrodynamic focusing, secondary flows are generated to strengthen the focusing in the vertical direction. In experiments, the chip was able to focus the sample flow with cross sections of 15 μm high and 8–30 μm wide at 5 m/s, under the condition of the sample flow rates between 10 and 120 μL/min. Instead of using the conventional elliptical Gaussian spot for optical detection, we used a specially designed BOE and obtained a 50 μm × 10 μm rectangular quasi-flat-top spot. The microflow cytometer combining the chip and the BOE was tested to count 3, 5, and 7 μm fluorescence microbeads, and the experimental results were comparable to or better than those derived from two commercial instruments.